Persistent bleeding in hemosiderotic superficial lymphatic malformation. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
A superficial lymphatic malformation often becomes evident following an intralesional hemorrhage; often the extravasated blood spreads in the surrounding skin giving rise to a target appearance. A case of intra- and perilesional hemorrhage characterized by the saving of the nipple area is described and its pathogenesis is discussed.